THE EFFECT OF NON-STARCH POLYSACCHARIDES DERIVED FROM DIFFERENT GRAINS ON PERFORMANCE AND DIGESTIVE ACTIVITY IN LAYING HENS - Hartini, S.; Choct, M. (Journal of the Indonesian Tropical Animal Agriculture, 2010)
An experiment was conducted to observe the effect of non-starch polysaccharides (NSP) onperformance and digestive activity of laying hens. Thirty-two ISA Brown hens were individually cagedand offered four diets (wheat-based, millrun-based, barley-based, and barley-enzymes diets) for 10weeks. The present experiment was assigned in a completely randomized design with 8 replicates perdietary treatment. Wheat- and barley diets caused significantly higher (P<0.05) viscosity than otherdiets. Increased viscosity caused lower digesta dry matter (DM) (P<0.01) and higher excreta moisture(P<0.05). The wheat diet did not cause a negative effect on intestinal starch digestibility, feed intake, andbird performance (P>0.05). Birds fed the barley-based diet had lower weight gain (P<0.05) and highercaecal weight (P<0.05) than those given other diets. Enzyme supplementation on barley dietssignificantly (P<0.05) reduced jejunal digesta viscosity and caecal weight, increased weight gain(P<0.05) and ileal digesta DM (P<0.01), and numerically reduced excreta moisture. The current studydemonstrated that NSP have a profound effect on digesta viscosity, performance, and digestive organs ofbirds; however, the NSP action may be modified by an interaction with each other and with other cellwallcomponents of grains in the gut. Enzyme supplementation reduced the negative effect of digestaviscosity.